Chromatin-Remodelling Complex NURF Is Essential for Differentiation of Adult Melanocyte Stem Cells. - Dana Koludrovic; Patrick Laurette; Thomas Strub; Céline Keime; Madeleine Le Coz; Sebastien Coassolo; Gabrielle Mengus; Lionel Larue; Irwin Davidson (PLoS Genetics, 2015)
MIcrophthalmia-associated Transcription Factor (MITF) regulates melanocyte and melanoma physiology. We show that MITF associates the NURF chromatin-remodelling factor in melanoma cells. ShRNA-mediated silencing of the NURF subunit BPTF revealed its essential role in several melanoma cell lines and in untransformed melanocytes in vitro. Comparative RNA-seq shows that MITF and BPTF co-regulate overlapping gene expression programs in cell lines in vitro. Somatic and specific inactivation of Bptf in developing murine melanoblasts in vivo shows that Bptf regulates their proliferation, migration and morphology. Once born, Bptf-mutant mice display premature greying where the second post-natal coat is white. This second coat is normally pigmented by differentiated melanocytes derived from the adult melanocyte stem cell (MSC) population that is stimulated to proliferate and differentiate at anagen. An MSC population is established and maintained throughout the life of the Bptf-mutant mice, but these MSCs are abnormal and at anagen, give rise to reduced numbers of transient amplifying cells (TACs) that do not express melanocyte markers and fail to differentiate into mature melanin producing melanocytes. MSCs display a transcriptionally repressed chromatin state and Bptf is essential for reactivation of the melanocyte gene expression program at anagen, the subsequent normal proliferation of TACs and their differentiation into mature melanocytes.